The Influence of Adopting Artificial Intelligence (AI) On Malaysia's Economic Environment - Caroline Geetha (Penerbit Universiti Malaysia Sabah, 2024)
This study aims to conduct a systematic review of the implications of adopting Artificial Intelligence (AI) on the economic landscape of Malaysia. Aligned with economic growth theories, the research underscores AI's pivotal role in transforming resources characterized by diminishing marginal returns into assets with increasing marginal returns. The analysis is multifaceted, addressing three fundamental perspectives. First, it examines AI adoption's impact on both microeconomic and macroeconomic dimensions. At the macroeconomic level, the study observes AI's influence on demand-pull and cost-push inflation, affecting overall price levels in the Malaysian economy. At the microeconomic level, AI adoption is linked to increased productivity and efficient resource allocation, leading to economies of scale. In an innovative and competitive business environment, AI adoption further enhances the quality of goods and services while ensuring competitive pricing strategies. Second, the study differentiates the positive and negative consequences of AI adoption across various sectors and demographic groups, providing specific examples of how different industries and population segments may benefit from or face challenges due to AI implementation. Finally, the analysis distinguishes the short-term and long-term impacts of AI adoption. In the short term, changes in employment, productivity, and consumer prices are identified, while the long-term analysis explores structural changes, including income redistribution and sustained productivity growth. The findings highlight the net positive impact of AI adoption in Malaysia, emphasizing that its benefits outweigh the costs. The study underscores the significance of government involvement in formulating policies and providing necessary infrastructure, aligning with Romer's theory of economic growth to drive successful and sustainable AI adoption for economic development.